Exploring Novel Methods to Achieve Systemic Delivery of SMN for Treatment of Spinal Muscular Atrophy - McFall, Emily (Université d'Ottawa / University of Ottawa, 2014)
Spinal muscular atrophy (SMA) is an inherited neurodegenerative disease caused by insufficient levels of the survival motor neuron protein (SMN), leading to progressive deterioration of α-motor neurons, onset of muscle atrophy and, in severe disease, death. We investigated whether reducing the size of Adenovirus (Ad) vectors, through use of a short fibre protein, could enhance delivery of a transgene to muscle and motor neurons after systemic delivery in vivo. Unfortunately, the biodistribution of the smaller Ad vector was unaltered compared to wildtype Ad, with most of the virus localizing to the liver. However, we determined Ad-derived SMN was efficiently packaged into cellular exosomes, suggesting a novel approach to protein delivery. We showed that exosomes naturally contain SMN both in vitro and in vivo and that exosomes can be used to deliver SMN to recipient cells. Further testing is required to establish if SMN-containing exosomes can function as an SMA therapeutic.
Keywords: Adenovirus